Chemoenzymatic Route to Oxyfunctionalized Cembranoids Facilitated by Substrate and Protein Engineering. Issue 46 (19th July 2018) - Le‐Huu, Priska; Rekow, Dominik; Krüger, Claudia; Bokel, Ansgar; Heidt, Tanja; Schaubach, Sebastian; Claasen, Birgit; Hölzel, Sebastian; Frey, Wolfgang; Laschat, Sabine; Urlacher, Vlada B.
Abstract: Cembranoids constitute a large family of 14‐membered oxygenated macrocyclic diterpenoids with potential as therapeutic agents. Selective late‐stage oxidations of cembranoid scaffolds remain a challenge for chemical catalysts but can be accomplished by enzymes. Here, a new chemoenzymatic route to oxyfunctionalized 14‐membered macrocycles including cembranoids is described. This route combines a metal‐catalyzed ring‐closing metathesis with a subsequent P450 BM3‐catalyzed hydroxylation and delivers cembranoid‐like analogues. Systematic substrate probing with a set of synthetic 14‐membered macrocycles revealed that the regioselectivity of a P450 BM3‐based biocatalyst increased with increasing ring rigidity as well as size and polarity of the exocyclic substituents. Enzyme regioselectivity could further be improved by first‐sphere active site mutagenesis. The V78A/F87A variant catalyzed hydroxylation of cembranoid‐ol (9 S / R )‐3 d with 90 % regioselectivity for C5 position. Extensive NMR analysis of Mosher esters and single crystal X‐ray structure determination revealed a remarkable diastereoselectivity of this P450 BM3 mutant depending on substrate stereochemistry, which led exclusively to the syn ‐cembranoid‐diols (5 S, 9 S )‐4 and (5 R, 9 R )‐4 . Abstract : Here comes the syn : Selective late‐stage oxidation of complex scaffolds is a challenging task. Combination of substrate engineering and protein design provided a P450 BM3 monooxygenase‐catalyzed oxidation of cembranoid analogues, which yielded syn ‐cembranoid‐diols with high diastereoselectivity (d.r.>95:5).